O‘RTA ASRLARda MARKAZIY OSIYODA JISMONIY TARBIYaning rivojlanish tarixi - Qaljanov, R.; Dauletnazarova, G.; Omirzakova, Q. (SCIENCE and SOCIETY, 2023)
The article deals with the development of physical education in the Middle Ages, the role of physical education, the treatises of Central Asian scholars on physical education, the sport of wrestling in the Alpomish, also it is presented information about the use of arrows, events held in the field of physical culture and sports today.